Repertuar muzyczny zapominany i przypominany w ewangelickim Wrocławiu - Jeż, Tomasz (Res Facta Nova, 2025)
If collective memory defines the identity of a community, then each of its transformations brings about the forgetting of certain elements of heritage, which in the new system of values turn out to be unwanted. However, even a very radical change in culture allows for the perpetuation of that part inherited from tradition which is sanctioned by means of a new system of meanings given to it. The most important turning point in the history of modern Breslau is rightly considered to be the time of the introduction of the Reformation in this city, which brought significant transformations of many forms of culture. These changes also concerned the musical repertoire, which was to serve the changing liturgical orders in the reformed churches of the Oder metropolis from 1524. The preserved sources inform us about how this process looked, documenting both the phenomenon of conscious abandonment of a certain resource of the repertoire (liturgical and vernacular), as well as the process of its recapitulation, carried out on the basis of well-thought-out culture-forming strategies. The documentation sources of both processes are analysed in light of the methodological pattern of oblivion figures proposed by Marc Augé.